Designing and development of phthalimides as potent anti-tubulin hybrid molecules against malaria - Singh, Vigyasa; Hada, Rahul Singh; Jain, Ravi; Vashistha, Manu; Kumari, Geeta; Singh, Snigdha; Sharma, Neha; Bansal, Meenakshi; Poonam; Zoltner, Martin; Caffrey, Conor R; Rathi, Brijesh; et al. (European journal of medicinal chemistry, 2022)
Constant emergence of drug-resistant Plasmodium falciparum warrants urgent need for effective and inexpensive drugs. Herein, phthalimide (Pht) analogs possessing the bioactive scaffolds, benzimidazole and 1,2,3-triazole, were evaluated for in vitro and in vivo anti-plasmodial activity without any apparent hemolysis, or cytotoxicity. Analogs 4(a-e) inhibited the growth of 3D7 and RKL-9 strains at submicromolar concentrations. Defects were observed during parasite egress from or invasion of the red blood cells. Mitochondrial membrane depolarization was measured as one of the causes of cell death. Phts 4(a-e) in combination with artemisinin exhibited two-to three-fold increased efficacy. Biophysical and biochemical analysis suggest that Pht analogs mediate plasmodial growth inhibition by interacting with tubulin protein of the parasite. Lastly, Phts 4(a-e) significantly decreased parasitemia and extended host survival in murine model Plasmodium berghei ANKA infection. Combined, the data indicate that Pht analogs should be further explored, which could offer novel value to the antimalarial drug development pipeline.
Keywords: Mice; Phthalimides; Antimalarial; malárie; Plasmodium berghei; Malaria; Animals; Drug discovery; Phthalimide analogs; Plasmodium falciparum; Tubulin; Drug resistance; antimalarika; myši; Antimalarials; zvířata; tubulin; ftalimidy